2016
DOI: 10.1038/srep26855
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum induced B-to-Z transition in self-assembled Y-shaped branched DNA structure

Abstract: Controlled conversion of right-handed B-DNA to left-handed Z-DNA is one of the greatest conformational transitions in biology. Recently, the B-Z transition has been explored from nanotechnological points of view and used as the driving machinery of many nanomechanical devices. Using a combination of CD spectroscopy, fluorescence spectroscopy, and PAGE, we demonstrate that low concentration of lanthanum chloride can mediate B-to-Z transition in self-assembled Y-shaped branched DNA (bDNA) structure. The transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Although Z-DNA formation requires extreme ionic strength (4 M NaCl), it is correlated with transcriptional activity. Recently, it was shown that lanthanide ions at millimolar levels were loaded to the grooves of DNA and stabilize the Z-DNA conformation with sequence sensitivity ( 39 ). It is unknown whether this is also the case for the observed phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Although Z-DNA formation requires extreme ionic strength (4 M NaCl), it is correlated with transcriptional activity. Recently, it was shown that lanthanide ions at millimolar levels were loaded to the grooves of DNA and stabilize the Z-DNA conformation with sequence sensitivity ( 39 ). It is unknown whether this is also the case for the observed phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…4b. 45,46 The specic surface area and pore diameter of neat PPY were 41 m 2 g À1 and 5.25 nm. The specic surface area increased to 81.7 and 107. nanocomposite remained mesoporous in nature.…”
Section: Brunauer-emmett-teller (Bet) Analysismentioning
confidence: 99%
“…The duplex DNA generally adopts right‐handed helices under physiological conditions and may change to left‐handed helices depending on the sequence and medium conditions ( B – Z transition) . The B – Z transition is supposed to play a role in the gene expression pathway and is applied to a molecular switch of a nanodevice .…”
Section: Figurementioning
confidence: 99%